Utility of Radial Scanning for the Identification of Arterial Hypervascularity of Hepatocellular Carcinoma on Gadoxetic Acid–Enhanced Magnetic Resonance Images. Issue 3 (May 2021) - Narita, Keigo; Nakamura, Yuko; Higaki, Toru; Nishihara, Takashi; Harada, Kuniaki; Takizawa, Masahiro; Shirase, Ryuji; Bito, Yoshitaka; Akagi, Motonori; Honda, Yukiko; Iida, Makoto; Awai, Kazuo
Abstract : Objectives: This study aimed to compare the accuracy of assessing the arterial hypervascularity of hepatocellular carcinoma (HCC) on dynamic computed tomography (CT) scans and gadoxetic acid (EOB)–enhanced magnetic resonance imaging (MRI) scans performed with radial sampling. Methods: We studied the images of 40 patients with hypervascular HCC. A radiologist recorded the standard deviation of the attenuation (or the signal intensity [SI]) in subcutaneous fat tissue as the image noise ( N ) and calculated the contrast-to-noise ratio (CNR) as follows: (CNR) = (n-ROIT − n-ROIL )/ N, where n-ROIT is the mean attenuation (or SI) of the tumor divided by the mean attenuation (or SI) of the aorta and n-ROIL is the mean attenuation (or SI) of the liver parenchyma divided by the mean attenuation (or SI) of the aorta. Results: The CNR was significantly higher on EOB-enhanced MRI than on dynamic CT scans. Conclusions: For the assessment of HCC vascularity, EOB-enhanced MRI scans acquired with radial sampling were more accurate than dynamic CT images.